1991
DOI: 10.1016/s0022-5347(17)38328-3
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Residual Cancer in Radical Prostatectomy Specimens in Stage a Prostate Cancer

Abstract: To assess the volume and distribution of residual cancer after transurethral resection of the prostate in stage A cancer patients 42 step-sectioned radical prostatectomy specimens were examined, and the volume, location, grade and extracapsular extension of the residual tumor were recorded. A total of 13 patients had stage A1 tumors (5% or less tumor in the transurethral resection specimen and a Gleason sum of 7 or less) and 29 had stage A2 disease. Residual cancer was present in the radical prostatectomy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Prostate cancer is a multifocal and heterogeneous disease with diverse histopathologic patterns. 13,[30][31][32] In evaluating a series of whole-mounted radical prostatectomies, Aihara et al 30 found that greater than half contained 3 different Gleason patterns. Recent studies have found that the volume of tumor present in biopsies does not correlate with the postoperative radical prostatectomy Gleason score, emphasizing the significance of small-volume, high-grade elements.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is a multifocal and heterogeneous disease with diverse histopathologic patterns. 13,[30][31][32] In evaluating a series of whole-mounted radical prostatectomies, Aihara et al 30 found that greater than half contained 3 different Gleason patterns. Recent studies have found that the volume of tumor present in biopsies does not correlate with the postoperative radical prostatectomy Gleason score, emphasizing the significance of small-volume, high-grade elements.…”
Section: Discussionmentioning
confidence: 99%
“…Stamey et al 16 noted that tumor volume (as determined by computer planimetry), percent Gleason grade 4-5, positive lymph nodes, and intraprostatic vascular invasion were associated with progression as defined by increasing PSA level. 16 Tumor progression occurred in 14% of men with tumor volumes in the range of 0.5-2.0 cm 3 , compared to 97% of men with tumor volumes greater than 12.0 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple histologic techniques have been utilized to assess tumor size since the gross features of prostatic carcinoma are subtle 1 and the tumors are often multifocal. [2][3][4] Maximum tumor diameter has been suggested as a fast, easy, and objective method of estimating the amount of tumor. Renshaw et al 5 demonstrated that measurements of the maximum diameter of the largest focus of tumor, the largest single tumor area, and the sum of the areas of two separate tumor foci correlated with tumor volume.…”
mentioning
confidence: 99%
“…Several studies [6,8,12,29,30,34,35] showed that the long arm of chromosome 7 is genetically unstable in prostate cancer and associated with a poor prognosis [12]. Moreover, Greene et al [36] detected gains of the 7p region in 10% of localized cancers and in 56% of recurrent and hormone-resistant prostate tumours, using comparative genomic hybridization.…”
Section: (+) Gain Of a Chromosome Copy (Trisomy); (-) Loss Of A Chrommentioning
confidence: 99%